Study on the effects of odourous emission from landfill activities to human - Nurul Asikin Mokthi (School of Environmental Engineering University Malaysia Perlis, 2011)
Odour is unpleasant smell considered as an important pollution issues. Odour from the landfill is one component of pollutants that effect the human environment. The source of odour generate from the decomposition of biodegradable waste in municipal waste. The project was to study the perception and effect of odour emission from landfill to the nearby resident. Survey was carried out within five km radius from the landfill. The 50 respondents participate in the survey. The meteorological factors such as wind speed and wind direction were also considered to assess the acceptance of the local community towards the smell nuisance.